Managerial Process and Organizational BehaviorScott, Foresman and Company, 1969 (499 Pages) - Filley, Alan C.; House, Robert J. (Academy of Management Journal, 1969)
The article reviews the book ?Managerial Process and Organizational Behavior,? by Alan C. Filley and Robert J. House.